The Effect of Peer Acceptance on Well-Being in Adolescents - Fuad Mubarok; Adi Cilik Pierewan (Jurnal Penelitian Humaniora, 2018)
This study was aimed at determining the impact of peer acceptance on well-being in adolescents. Respondents used in this study were teenagers in the city of Yogyakarta with age range of 14-15 years old (N = 385). In this study, the researcher used an instrument in the form of a well-being by Ryff questionnaire that was modified according to the social and cultural conditions in the city of Yogyakarta to measure well-being in respondents used. On the scale of peer acceptance, researchers use sociometry with roster and rating modeling. The hypothesis proposed in this study was that peer acceptance could influence well-being in adolescents. Reliability analysis on the instrument used was carried out using Cronbach's Alpha analysis. This study used simple regression to determine the effect of peer acceptance on well-being in adolescents. The result shows that peer acceptance has an influence on well-being in adolescents. Although the effect produced was not significant, but it proves that it is quite important for adolescents to be accepted in their social environment to be able to obtain a well-being situation in themselves.Keywords: peer acceptance, well-being, adolescent